Lead, now, go! (LNG): the Shtokman field and Gazprom's challenging partnership with Total and Statoil. Issue 6 (2nd November 2018) - Loe, Julia S. P.
Abstract: In the early 2000s, developing liquefied natural gas (LNG) was declared a priority by the Russian state-controlled energy company Gazprom. As Gazprom had limited experience of LNG production, a logical solution was to establish partnerships with foreign companies. Despite ambitious goals, no major Gazprom-led LNG projects have emerged so far. While this can mainly be explained by market fall-out, scholars have also pointed to weaknesses in Gazprom's approach to foreign partners. This article analyses the partnership dynamics between Gazprom, Total, and Statoil in Russia's most ambitious LNG production project, the Shtokman field in the Barents Sea. The three companies established a partnership to develop the field in 2008, but only four years later the project was shelved. In addition to objective parameters, this paper finds that some of the challenges to the partnership resulted from differing norms, ideas, and world-views. These difficulties might, however, have been overcome had the field been commercially viable.